A STUDY OF SEASONAL ALLERGIC RHINITIS IN HAZARA DIVISION - Ghani, Rahman; Nabi, Ghulam; Ghazal, Saadia (Journal of Ayub Medical College Abbottabad, 1990)
ABSTRACT All the cases diagnosed as allergic rhinitis in the ENT outpatient of DHQ hospital Abbottabad over a period of one year were included in a study of the pattern of seasonal allergic rhinitis in Hazara division of NWFP, Pakistan. Maximum cases out of total 56 over a year were found in March (n=20) & April (n=30). In 90% of these cases history of other associated allergies was also present while the rest of the cases did not show any such association. Out of the total 56 cases, 26 patients were females and the rest were males. Most of the patients were below 40 years of age. Pollens seem to be the major allergens in this area especially those of the poplar and pine trees.